2019
DOI: 10.1021/acsomega.8b02199
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of a Nontargeted Boost for a CXCR4-Targeted Magnetic Hyperthermia Treatment of Cancer Cells

Abstract: We investigate the effectiveness and safety of a novel magnetic hyperthermia (MHT) protocol, whereby a pretreatment with nontargeted magnetic nanoparticles (MNPs) is used to boost the subsequent iron loading of cancer cells by the targeted immuno-modified MNPs. As a model example, LN229 cancer cells express specific cell-surface receptors (CXCR4) at levels sufficient for diagnostic identification but insufficient for achieving 100% effective monotherapeutic MHT based on CXCR4-targeted MNPs. The nontargeted boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…There are indications of the existence of distinct thermal susceptibility between normal and cancer cells [ 20 , 21 ]. However, this is only true for a certain range of temperatures and it does not exclude the occurrence of side effects mediated by nanomaterials (NMs).…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
See 2 more Smart Citations
“…There are indications of the existence of distinct thermal susceptibility between normal and cancer cells [ 20 , 21 ]. However, this is only true for a certain range of temperatures and it does not exclude the occurrence of side effects mediated by nanomaterials (NMs).…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
“…Fibroblasts, either from mouse origin [ 22 , 23 , 24 , 25 ] or from human [ 26 , 27 , 28 ] origin, are commonly used for this end. For targeted MHT studies, it may be more useful to use a cell line with a lower or even negative expression of the selected target, as this allows to simultaneously prove the selectivity of the treatment [ 21 , 25 ]. This type of study is particularly relevant when the selected target is also widely expressed in normal cells.…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
See 1 more Smart Citation
“…When BT‐474 cells are treated with magnetic nanoparticles and mitomycin‐C in the presence or absence of hyperthermia, it is reported that hyperthermia intensifies inhibitory effects of nanoparticles and mitomycin‐C on the expression levels of MDR‐associated proteins . Inactivation of drug detoxification mechanisms, increase in the drug uptake, induction of apoptosis, enhancement of drug cytotoxicity, and reduction in cell membrane localization of MDR proteins are other effects mediated by hyperthermia, which circumvent MDR in various cancers …”
Section: Novel Strategies Against Mdrmentioning
confidence: 99%
“…83 Inactivation of drug detoxification mechanisms, increase in the drug uptake, induction of apoptosis, enhancement of drug cytotoxicity, and reduction in cell membrane localization of MDR proteins are other effects mediated by hyperthermia, which circumvent MDR in various cancers. 84 The application of ultrasound therapy to enhance therapeutic efficacy against cancer cells has been the subject of various clinical investigations. This strategy has been applied as a hyperthermia-induction agent for direct treatment of tumors or as adjuvant therapy to increase the therapeutic efficacy when combined with chemotherapeutics.…”
Section: Physical Approaches To Overcome Mdrmentioning
confidence: 99%